Infrared motion detection and electromyographic gesture recognition for navigating 3D environments. (May 2018) - Chen, Keyu; Liang, Hai‐Ning; Yue, Yong; Craig, Paul
Abstract: This research explores the suitability and effectiveness of two relatively new types of input device for navigating 3D virtual environments. These are infrared motion detection, like the Leap Motion tracker, and electromyographic gesture recognition, like the Myo Armband. Despite the introduction of a variety of new input devices intended to provide a more natural interaction experience, navigation within 3D virtual environments is still normally done on more traditional control devices such as game controllers or the keyboard–mouse combination. This study investigates the potential of new devices to support navigation in 3D environments through an experiment conducted with 27 participants using three different types of input devices to play a ball‐balancing maze‐like game. The input devices tested are a standard game controller, a Leap Motion tracker for infrared motion detection, and the Myo Armband for electromyographic gesture recognition. Results demonstrated the real potential of both types of device to support navigation interaction within 3D environments. Abstract : We studied the performance of two kinds of new input devices, mid‐air and muscle‐based, in navigation tasks in a 3D virtual environment. Even though subjects at the beginning did not perform well with these devices when compared with a familiar, regular game controller, the gap in performance became smaller as they got familiar with the two new devices.